PENGARUH PEMBERIAN AIR KELAPA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KANGKUNG DARAT (Ipomoea reptans) - Benyamin Edo; Murdaningsih Murdaningsih (AGRICA, 2018)
This study aims to determine the effect of doses of coconut water on the growth and yield of land water spinach. The use of doses of coconut water as a treatment tested consists of K0 = Control; K1 = 56.68 liters / ha; K2 = 113.37 liters / ha; K3 = 170.05 liters / ha; K4 = 226.74 liters / ha. The results of the study addressed the use of 226.74 liters / ha of coconut water doses which had a very significant effect on all observation variables. Where an increase in the dose of coconut water affects the increase in the average percentage of plant height of 5.27%, the number of leaves is 4.58%, the fresh weight of ground water spinach per plant is 0.26% and the weight of land spinach per hectare is 0.26%